Contextual effects on attributing minds to older adults - Brittany S. Cassidy; Jonathan T. Ojeda (Current Research in Ecological and Social Psychology, 2024)
Elder abuse is a growing worldwide problem. The dehumanization of older adults likely contributes to elder abuse as it relates to a lower standard of care afforded to them as well as perpetuates negative attitudes and institutional policies affecting them. Here, we examined mind attributions of older adults receiving care given that mind denial relates to the perpetuation of harm against human agents. We show that living situation is a potent contextual cue affecting mind attributions toward older adults. Older adults receiving more external support and care in their overall living situations were attributed less mind, an effect due to their being attributed limited attributed agentic relative to experiential mental capacities (Experiment 1). Limited attributed agentic versus experiential capacities also emerged for older adults in care facilities to receive cognitive, but not physical, rehabilitation after acute medical emergencies (Experiments 2 and 3). This cognitive rehabilitation effect generalized to younger adults, although older adults were attributed less mind overall (Experiment 3). Showing consequences of limited inferred mental agency, attributed agentic capacities positively related to beliefs that rehabilitation would be successful (Experiment 3). All effects emerged when controlling for variability in aging-related prejudice, suggesting a broad emergence that could substantially affect older adults’ lives. These findings suggest that older adults in need of care are attributed limited agentic capacities that are necessary for people to believe in the efficacy of their care.